Thermal comfort and daylight assessment of vernacular house in Amaravati, Andhra Pradesh - Karthik Chadalavada; Kranti Kumar Myneni
Vernacular architecture, deeply rooted in local traditions, reflects the socio-cultural and climatic influences of its region. However, modernization and structural modifications have led to changes in indoor thermal conditions and daylighting. This study evaluates thermal comfort and daylight performance in a traditional vernacular house in Amaravati, Andhra Pradesh, emphasizing the role of passive design strategies in enhancing indoor environmental quality (IEQ). Using Design Builder software, this study assesses the impact of passive cooling techniques and daylight optimization in a heritage dwelling. The results indicate a 20% improvement in thermal comfort due to passive strategies, but a 25% reduction in natural lighting due to structural modifications. This highlights the need for context-specific retrofitting strategies that balance thermal and visual comfort while preserving the architectural integrity of heritage structures. This is the first study to quantitatively assess passive techniques for improving IEQ in vernacular houses of Amaravati, contributing to sustainable design and heritage conservation.